Artillery fire control based on artificial intelligence algorithm of unmanned aerial vehicle - Azad Agalar Bayramov; Samir Suleyman Suleymanov; Fatali Nariman Abdullayev (Institute of Advanced Engineering and Science, 2026)
The article presents the developed artillery fire remote control complex using unmanned aerial vehicles (UAVs) based on an artificial intelligence (AI) algorithm. The developed complex for artillery fire control includes sensor modules for assessing the environment, collecting and processing information, planning and decision-making, and developing a command for the commander of an artillery battalion, division, or brigade. The main advantage of the developed artillery fire control system using UAVs based on an AI algorithm is the most rapid decision-making without human intervention, based on a quick assessment of the environment, the type of enemy weapons, and their category of importance, and an assessment of the distance to the enemy’s military arms. An algorithm is proposed to minimize the power of artillery fire to suppress the enemy.